Genetic variation in gp 120 V1?V2 and neutralization sensitivity of HIV-1 subtype C isolates from children with rapid and slow disease progression - Choge, Isaac Ang' Ang' A (My University, 2003)
This project explore genetic variation and antibody neutralization sensitivity in gp 120 V1/V2 and C2-V5 region amongst HIV-1 subtype C pediatric isolates. Isolates from 25 slow progressing children and 16 rapid progressing infants were used in subtyping and quasispecies analysis performed with a novel V1/V2 heteroduplex mobility assay (HMA)
a dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg. for the Degree of Master of Science in Medicine (Virology) Johannesburg,. 2003
Keywords: HIV Envelope Protein gp120; HIV-1; Child; DNA